Confronting the Challenges of University Vocational Technical Education in Uganda - Agole , Peter; Kerre , Bonneventure; Okaka , Wilson (African Journal of Education,Science and Technology (AJEST), 2022)
This paper presents the major institutional, community, national, and regional challenges of promoting effective vocational-technical education training (TVET) system in line with the 2030 SDG 4 with a focus on Uganda. Uganda has been faced with several attempts to reform the vocational education system and the country has continued to meet various levels and bases of political social-economic and environmental challenges. The objectives of the paper are to examine the political challenges facing TVET in Uganda; assess the social factors that have affected the prospect of TVET in the country, and establish the major economic factors that have negated the planning of vocational education in Uganda and discuss the common environmental issues that have affected the success planning of vocational education of the country, this paper was informed by policy analysis and systematic literature review with a focus on documents obtained from the Ugandan government and national vocational institutions in the country. More information was obtained from internet sources, new bulletin, e-mail discussion experiential learning and informal discussion with key informants on the subject. So far, preliminary results have indicated that enabling political, social, environmental, and economic f actors are critical for the productive performance of successful national TVET planning in Uganda. In addition, it is imperative to promote social, economic, environmental, and political commitment at the top level for a prudent inclusive TVET system, curriculum planning envisaged by the SG4. The roles of public-private community partnerships (PPCP) should be well planned, funded, coordinated, motivated, and constantly fully enhanced for effective TVET implementation in the country.